(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India’s car industry is one of the world’s largest and constantly growing industries. In the initial phase, the Indian automobile industry followed and influenced Western trends and technologies. However, the Indian car industry and market can generate its own uniqueness during the recent period. New product launches on the Indian market have recently aligned themselves more with the requirements of Indian customers than with product launch or configuration on Western markets. Home-grown car manufacturers and MNCs make significant efforts to innovate products that meet Indian customer requirements. However, the automobile industry will have to do more to achieve success in the Indian car market than the current level of effort and innovate more. Innovative consumer behavior depends on Consumer innovatively. Innovativeness of the consumer refers to newness consumption. Since its launch in the late 18th century, the automobile industry has seen the Innovative. Many innovators have not even seen the light of production in the automobile industry. However, it often takes time to get the consumer accept the one that reaches the market. It further describes in Dharwad district in Karnataka state, the innovative automobile industry. The consumer behavior with each Innovative can be seen to be different. There are several innovative features in the cars that were built by design. But in India this is not the case. In India, the importance to advanced technology and safety is not yet understood. This represents the dedication of the state to further growth in the automobile sector and to be the largest Karnataka’s automobile Industrial in India.